2009
DOI: 10.1021/nl802853e
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Edge Effects on the Intrinsic Loss Mechanisms of Graphene Nanoresonators

Abstract: We utilize classical molecular dynamics simulations to investigate the intrinsic loss mechanisms of monolayer graphene nanoresonators undergoing flexural oscillations. We find that spurious edge modes of vibration, which arise not due to externally applied stresses but intrinsically due to the different vibrational properties of edge atoms, are the dominant intrinsic loss mechanism that reduces the Q-factors. We additionally find that while hydrogen passivation of the free edges is ineffective in reducing the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
133
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 96 publications
(146 citation statements)
references
References 23 publications
10
133
1
2
Order By: Relevance
“…The idealized monolayer result, corresponding to M1, is reproduced from Kim and Park. 10 As expected, the Q-factors for M1, which neglects both interlayer friction and attachment losses, are the largest for all temperatures, and that the Q-factor decays following a 1 / T relationship. More interesting are the double layer ͑M2͒ and monolayer on silicon ͑M3͒ results, which are the focus of the present work.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…The idealized monolayer result, corresponding to M1, is reproduced from Kim and Park. 10 As expected, the Q-factors for M1, which neglects both interlayer friction and attachment losses, are the largest for all temperatures, and that the Q-factor decays following a 1 / T relationship. More interesting are the double layer ͑M2͒ and monolayer on silicon ͑M3͒ results, which are the focus of the present work.…”
supporting
confidence: 78%
“…The first model ͑M1͒ was a circular graphene monolayer with a diameter of 56.8 Å, which consisted of 979 carbon atoms. All atoms outside a radius of 21.3 Å were fixed due to previous MD calculations, 10 which showed that spurious edge vibrational modes are one of the key factors for the low Q-factors of graphene sheets that have been observed experimentally. 3,7,11 M1 constitutes the benchmark, idealized model for comparison with the other two models as interlayer friction and attachment losses do not exist for this model.…”
mentioning
confidence: 99%
“…Edge reconstructions have been observed experimentally [25], which can be attributed to the thermal energy localized by the edge vibrations [26,27]. Edge vibrations were also found to be responsible for the larger energy dissipation in graphene nanomechanical resonators [28,29]. It was found that edge effects are the dominant factor for the friction between neighboring nanotubes in multi-wall carbon nanotubes [30], and a piece of graphene can be driven from a softer regime to the stiffer regime due to the edge effect [31].…”
Section: Introductionmentioning
confidence: 95%
“…Yet, control of 3D multilayered GO structures is important for a number of applications, including electrolytes within super-and hybridcapacitors 24 and batteries (ionic transport) 25 , mechanical actuators 26 that convert external stimuli such as thermal, light, electrical 27,28 , or chemical energy to mechanical energy 29 . In electromechanical resonators for example, the actuation depends on variation of humidity and/or temperature 30 . In supercapacitors, the ion transport is controlled by the size of openings (i.e.…”
Section: Introductionmentioning
confidence: 99%